Football matches: Decision making in betting. (3rd December 2019) - Chalikias, Miltiadis; Kossieri, Evangelia; Lalou, Panagiota
Abstract: The aim of this paper is to approach the teaching of the Poisson distribution in a friendly and amusing way. It constitutes a common practice to adopt the main probability distributions in order to predict results of sport events and to estimate the win return of betting activities (Chalikias 2009). In particular, by using the Poisson distribution, we can calculate the probability of the final score in a football match, and then we can compare this probability with the values that various betting companies offer. Combining this information with the average of goals for both, it is possible to make a decision as to which betting company is more profitable for the betting players. The case study of the English Premier League is examined.